STRATEGIC MODEL FOR IMPROVING THE PERFORMANCE AND GROWTH OF LOCAL FOOD SME’s IN EAST NUSA TENGGARA - Enike Tje Yustin Dima; Alya Elita Sjioen; Engelbertus G. Ch. Watu; Apryanus Fallo; Konstantinus Su; Maria Augustin Lopes Amaral (Universitas Gunadarma, 2025)
Small and medium-sized enterprises (SME’s) in the local food sector in East Nusa Tenggara play an important role in driving regional economic growth while preserving local wisdom. This study aims to analyze the influence of market sensing, innovativeness, knowledge, motivation, partnership quality, and IT capability on the growth of local food SME’s. The research method employed is a quantitative approach through a survey of 165 SME’s operators, with data analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The analysis results indicate that market sensing, knowledge, motivation, and partnership quality have a significant impact on SME’s growth. Conversely, innovativeness and IT capability do not have a significant impact. These findings emphasize that the ability to understand market needs, manage business knowledge, maintain entrepreneurial motivation, and establish quality partnerships are the primary determinants of the growth of local food SME’s. Meanwhile, limited resources, low digital literacy, and local consumer preferences for traditional products are factors that explain the weak contribution of innovation and information technology. This study contributes to the development of literature by reaffirming the relevance of the Resource-Based View and Dynamic Capabilities View theories in the context of SME’s in island regions. Practically, business actors need to strengthen market sensing, enhance knowledge capacity, and build strategic partnership networks. Further studies are recommended to examine the role of mediating factors, policy support, and the dynamics of SME’s growth in the long term.